ANGIOTENSINERGIC AND CHOLINERGIC RECEPTORS OF THE SUBFORNICAL ORGAN MEDIATE SODIUM INTAKE INDUCED BY GABAergic ACTIVATION OF THE LATERAL PARABRACHIAL NUCLEUS - Roncari, C. F. [UNESP]; David, R. B. [UNESP]; Johnson, R. F.; Paula, Patricia Maria de [UNESP]; Colombari, Débora Simões de Almeida [UNESP]; De Luca, L. A. [UNESP]; Johnson, A. K.; Colombari, Eduardo [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2014)
Bilateral injections of the GABA(A) agonist muscimol into the lateral parabrachial nucleus (LPBN) induce 0.3 M NaCl and water intake in satiated and normovolemic rats, a response reduced by intracerebroventricular (icv) administration of losartan or atropine (angiotensinergic type 1 (AT(1)) and cholinergic muscarinic receptor antagonists, respectively). In the present study, we investigated the effects of the injections of losartan or atropine into the subfornical organ (SFO) on 0.3 M NaCl and water intake induced by injections of muscimol into the LPBN. In addition, using intracellular calcium measurement, we also tested the sensitivity of SFO-cultured cells to angiotensin II (ANG II) and carbachol (cholinergic agonist). In male Holtzman rats with cannulas implanted bilaterally into the LPBN and into the SFO, injections of losartan (1 mu g/ 0.1 mu l) or atropine (2 nmol/0.1 mu l) into the SFO almost abolished 0.3 M NaCl and water intake induced by muscimol (0.5 nmol/0.2 mu l) injected into the LPBN. In about 30% of the cultured cells of the SFO, carbachol and ANG II increased intracellular calcium concentration ([Ca2+](i)). Three distinct cell populations were found in the SFO, i.e., cells activated by either ANG II (25%) or carbachol (2.6%) or by both stimuli (2.3%). The results suggest that the activation of angiotensinergic and cholinergic mechanisms in the SFO is important for NaCl and water intake induced by the deactivation of LPBN inhibitory mechanisms with muscimol injections. They also show that there are cells in the SFO activated by both angiotensinergic and cholinergic stimuli, perhaps those involved in the responses to muscimol into the LPBN. (C) 2013 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: sodium appetite; parabrachial nucleus; subfornical organ; AT(1) receptor; muscarinic receptor